Internet and people with intellectual disability: an approach to caregivers' concerns, prevention strategies and training needs - Esther Chiner; Marcos Gómez-Puerta; M. Cristina Cardona-Moltó (Springer, 2017)
The aim of this study was to explore caregivers' views about the risks of the Internet for people with intellectual disabilities and their preparation and ability to use prevention strategies to address them. The participants (20 family members and 24 staff members) belonged to a non-profit association working with people with developmental and intellectual disabilities and were asked to respond to a questionnaire about Internet safety and risks. Findings show some concerns from caregivers with regard to the use of the Internet by people with intellectual disabilities and suggest that this group is more vulnerable to online risks. Participants use different kinds of strategies to prevent the risks but they have not received any formal training. They think that this training should come from the Administration and other organisations. Some differences were found between family and staff members' responses. Training programmes for all the groups involved in this process (i.e. people with intellectual disabilities, staff and family members) should be designed, implemented and assessed to promote the inclusion of people with intellectual disabilities in the digital arena.